Same-Day Desensitization in Patients Who Experience Their First Reaction to a Platin Agent at the Oncology Day Unit: A Pilot Study to Safely Include This Technique Within the Multidisciplinary Pathways for the Diagnosis & Management of Hypersensitivity to Platin Agents - Borrás Cuartero, Julián; Farzanegan Miñano, Roxana; Torres Gorriz, María Cruz; Germán Sánchez, Adrián; Aznar, Raquel Cervera; Raducan, Isabela; Castelló Carrascosa, Jose Vicente; Sanchez Hernandez, Alfredo; Enrique, Ernesto (Frontiers in Allergy, 2022)
One of the main objectives when assessing patients who react to antineoplastics must be to ensure that they receive the required treatments without delay. From January to July 2021, at the Allergy Department at the Provincial University Consortium Hospital a pilot study was performed in which those patients suspected of having suffered a type I hypersensitivity reaction (grade 1 or 2) following Brown's anaphylaxis severity grading to a platin agent at the Provincial University Consortium oncology day unit, and once the reaction was properly treated and completely resolved, were subjected to a new procedure named as Same-Day Desensitization, which consists in the reintroduction and administration of full chemotherapy dose by allergists on the same day of the reaction by following the 1 bag/10 step protocol, looking forwards to systematize same-day reexposure using Same-Day Desensitization, doing it in the safest way possible. In total, 9 oncological patients suspected of having suffered a type I hypersensitivity reaction (grade 1 or 2) to a platin agent received total dose administration the same day of the initial reaction by following Same-Day Desensitization 1 bag/10 step protocol, without presenting further reactions. The manuscript describes a new approach in the use of Rapid Drug Desensitizations in reactive oncologic patients in treatment with platin agents, presenting the first 9 cases of oncologic patients who have been submitted to this procedure.